PENGARUH TINGKAT PENDIDIKAN TERHADAP KEPUTUSAN MENJADI NASABAH DI PT. BANK MUAMALAT INDONESIA, TBK., CABANG PEMBANTU SIBUHUAN - Batubara, Sarmiana (At-tijaroh: Jurnal Ilmu Manajemen dan Bisnis Islam, 2017)
This study determine whether there is influence of education level to the decision to become a customer in PT. Bank Muamalat Indonesia,Tbk., Auxiliary Branch Sibuhuan and how big the influence are. The research is quantitative explainatory, data collected using a questionnaire with sample 32 people. From the research results show the influence of education level to the decision to become a customer in PT. Bank Muamalat Indonesia, Tbk., Sibuhuan Sub-branch is very positively influential. Great influence of education level to the decision to become a customer in PT. Bank Muamalat Indonesia, Tbk., Sibuhuan Sub-branch is using the product momant calculation, it turns out the correlation number between variable X and variable Y is not negative sign, meaning that between the two variables there is positive correlation (correlation that goes unidirectional). By considering the amount of rxy (ie = 0.155), whose magnitude ranges from 0.00-0.19 means between variables X and Y are very weak or very low correlation. Interpretation by using Table Value "r": degrees of freedom (df) is df = N - 2 = 32 - 2 = 30. After obtained df then checked table value of correlation coefficient table at significance level 5% and 1%. With df of 30 at significance level 5% obtained rtabel = 0,361 and at 1% significance level obtained rtabel = 0,463. Based on this it is clear that rxy rtabel both at the level of significance of 5% and 1% (0.155 0.361 or 0.463 0.155). Thus Ha is accepted while Ho is rejected. So the level of education to the decision to become a customer in PT. Bank Muamalat Indonesia, Tbk., Sibuhuan auxiliary branch has a moderate influence.